Accuracy and User Satisfaction for an Audible Prescription Reader Among Adults With Low Vision and Blindness. (September 2022) - Jackson, Leslie; Bradway, Trevor; Lefevers, Victoria; Li, Yulun; Olson, Annabel
Introduction: Research is needed to support accuracy and safe self-management of prescriptions among individuals living with low vision or blindness. This study evaluated user accuracy & satisfaction with the ScripTalk® device, an audible prescription reader, among participants with low vision and blindness.Methods: This mixed methods study utilized snowball and convenience sampling through low vision support groups in Indiana. Researchers trained 23 participants (69.6% female, 30.4% male, M age = 64.04, SD  = 14.7 years) to use the ScripTalk® device for reading three empty prescription bottles, equipped with radio-frequency ID labels. Accuracy represented correct responses to 12 questions about the labels' content. The QUEST 2.0's Device Subscale (intraclass correlation coefficient = 0.82) evaluated user satisfaction with the device. Participants answered six qualitative questions about their perceptions of the device.Results: Statistical analysis indicated highest frequencies of satisfaction occurred for Ease in Adjusting (100%), Comfort (100%), Ease of Use (95.6%), and the Weight (95.6%) of the device. Spearman rank order correlation coefficient tests revealed inverse relationships between participants' accuracy rates and their satisfaction with the device's durability (rho = −0.690, p  < .001) and safety & security (rho = −0.834, p  < .001). Participants perceived the device as easy to use, adjustable, comfortable, and lightweight for reading prescription labels. However, the auditory quality posed challenges to identify unfamiliar prescription names. Health care professionals may need to provide additional training and practice opportunities with audible prescription readers to support consumers with low vision or blindness, particularly when new medications are prescribed.